2011
DOI: 10.1111/j.1439-0426.2011.01919.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin structure studies and molecular identification of the Atlantic cod Gadus morhua L. of unique golden pigmentation from the Svalbard Bank

Abstract: Summary An Atlantic cod, Gadus morhua L., with unique golden pigmentation was caught during a commercial trawl on the Svalbard Bank. Stomach content analysis excluded the possibility of golden pigmentation resulting from diet. Skin morphology, mitochondrial and molecular species markers and also the concentration of melatonin (MEL) were examined. Skin samples from five areas below and above the lateral line contained correctly developed melanophores, but their distribution was different from those observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The light-microscope examination of the semithin vertical sections of the dorsal skin melanophores of B. melanostictus indicated that melanophores are present dominantly in the subepidermis, called as subepidermal melanophores. Dermal melanophores in this species have been found in very less number and remain situated just below the subepidermal layer, although some melanophores occur deeper in the dermis, as revealed by Kijewska et al [ 27 ] in the Atlantic cod, Gadus morhua . We have examined the effects of berberine per se , and with its specific antagonists and agonists on toad-skin subepidermal melanophores using the electron microscope, and found that berberine stimulated the process of melanization, as well as increased the number of melanin-loaded dendrites of the subepidermal melanophores of the toad, B. melanostictus .…”
Section: Discussionmentioning
confidence: 63%
“…The light-microscope examination of the semithin vertical sections of the dorsal skin melanophores of B. melanostictus indicated that melanophores are present dominantly in the subepidermis, called as subepidermal melanophores. Dermal melanophores in this species have been found in very less number and remain situated just below the subepidermal layer, although some melanophores occur deeper in the dermis, as revealed by Kijewska et al [ 27 ] in the Atlantic cod, Gadus morhua . We have examined the effects of berberine per se , and with its specific antagonists and agonists on toad-skin subepidermal melanophores using the electron microscope, and found that berberine stimulated the process of melanization, as well as increased the number of melanin-loaded dendrites of the subepidermal melanophores of the toad, B. melanostictus .…”
Section: Discussionmentioning
confidence: 63%
“…The aetiology of abnormal xanthochromism in fish is not always clear. For example, the condition has been observed in association with overt skin pathologies (chromatophoromas and chromatophore hyperplasia) in yellowtail rockfish S. flavidus (Ayres, 1862) (Okihiro, Whipple, Groff, & Hinton, 1993) and flag rockfish S. rubrivinctus (Jordan & Gilbert, 1880) (Phillips, 1957), a diet rich in carotenoids (Leclercq, Taylor, & Migaud, 2010), hormonal imbalance (Burton, 2010), and possibly interspecific hybrids (Kijewska, Wiecaszek, Kalamarz-Kubiak, Szulc, & Sobecka, 2012). However, in the vast majority of cases, the condition is generally thought to be caused by a non-pathological genetic mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Entre las posibles causas de esta alteración/aberración se han sugerido, tanto en peces como en otros grupos de organismos, aspectos ecológicos [e.g., una dieta rica en carotenoides (Leclercq et al, 2010) o deficiente en vitaminas C y E (Simon, Joyeux, & Gasparini, 2011), así como la hibridización interespecífica (Kijewska, Wiecaszek, Kalamarz-Kubiak, Szulc, & Sobecka, 2012)], patológicos [cromatoforomas (tumores compuestos por cromatóforos) o cromatóforos hiperplásicos (e.g., Okihiro, 1993;Noga, 2010)], fisiológicos [e.g., desbalances hormonales (Burton, 2010), siendo la epinefrina una de las más importantes (Irigoyen-Arredondo et al, 2018) y otros desordenes neuroendocrinos (Noga, 2010)] y genéticos [i.e., mutaciones diversas y, usualmente, múltiples en uno o varios de los genes (usualmente recesivos) involucrados en (1) la formación, desarrollo y regulación de células pigmentarias, (2) la síntesis y producción de los diversos pigmentos cutáneos, y (3) la translocación y expresión de estos pigmentos, entre otros (Odenthal et al, 1996;Leclercq, 2010 et al;Kijewska et al, 2012)]. Otros factores que han sido señalados como posibles causas o desencadenantes de tal afectación son las infecciones parasíticas (Irigoyen-Arredondo et al, 2018), la presencia de contaminantes (Macieira, Joyeux, Chagas, 2006;Irigoyen-Arredondo et al, 2018) o la presencia de heridas provocadas por otros organismos durante interacciones antagónicas (Colman, 1972), no obstante, no se ha probado una correlación directa entre estas y la anomalía pigmentaria en cuestión.…”
Section: Discussionunclassified